Hadis-hadis Tentang Puasa Sunnah (Analisis Sejarah) - Dame Siregar (Institut Agama Islam Negeri Padangsidimpuan, 2021)
Dawud fast, baid or fasting 3 days every month (part of the opinion of the legal fasting is sunnah) should be mandatory fasting before the Romadon fast. The mandatory fast of the Prophet Dawud was translated into obligatory fasting, and obligatory fasting of the Prophet was translated as mandatory romadon fast. Fasting sunnah rojab, nisfu sya'ban, six days of the month of shawwal, tarwiyyah, arofat, 'asyuro, tasu'a. has been included with the fast Monday Thursday and jumu'ah. The sunnah fast that continues is the Monday and Thursday fast and jumu'ah. Fasting on Friday requires fasting on the previous day, namely Thursday, if not, then fasting afterwards is on the Saturday. This type of fasting means the meaning of الصيام in al-Baqoroh verse 183. The word الصيام in the translation of the Koran is fasting romadon. The types of fasting should be: Mandatory fasting, such as romadon nazar, qodo and kaffaroh. Sunnah fasting is fasting Monday Thursday and jumu'ah every week except the day coinciding with the day of 'idil fitr or adha and the day of tasyriq (11,12 and 13 dzulhijjah)